ANALISIS PERAN MEDIA AUDIOVISUAL TERHADAP DIMENSI KOGNITIF PROFIL PELAJAR PANCASILA DALAM MATERI AKHLAK - Alim Billah; Segar sukrun; Ayu Amelia; Anggun Kurnia Sari; Anggi Hanifah Anjani; Nailah Apta Ardelia; kheysya Suci Andini; Rita Sugiarti; Sri Maryati (STKIP Subang, 2026)
This study aims to analyze the role of audiovisual media on the cognitive dimension of the Pancasila Student Profile in teaching morals to elementary school students. The use of audiovisual media, such as animated videos, is considered capable of presenting material in a more engaging and concrete manner, thus facilitating students' understanding of moral values. This study focused on fourth-grade elementary school students in Phase B, where students' cognitive thinking skills begin to develop, including understanding, remembering, and applying concepts in everyday life. The analysis shows that audiovisual media plays a positive role in improving students' cognitive abilities, particularly in understanding, analyzing, and internalizing moral values in accordance with the Pancasila Student Profile.